05/23/2014, 11:12 PM

More precisely :

Uniqueness or at least a strong condition :

Let B2 > B1 > e^(1/e).

Base independance :

r > 0

Define for base C :

exp_C(z) = c^z

a [r]_C b = b [r]_C a = exp_C^[r]( exp_C^[-r](a) + exp_C^[-r](b) )

Conjecture :

a [r]_B2 b = b [r]_B2 a = exp_B2^[r]( exp_B2^[-r](a) + exp_B2^[-r](b) ) = a [r]_B1 b = b [r]_B1 a = exp_B1^[r]( exp_B1^[-r](a) + exp_B1^[-r](b) )

Or simply : a [r]_B2 b = a [r]_B1 b.

Remark : its known to be true for r a positive integer. (it fails for r = -1 though )

Unfortunately I lost some data concerning this idea.

So if you see it mentioned here before , plz let me know.

I am also intrested in other " base independance " equations.

https://sites.google.com/site/tommy1729/...e-property

regards

tommy1729

Uniqueness or at least a strong condition :

Let B2 > B1 > e^(1/e).

Base independance :

r > 0

Define for base C :

exp_C(z) = c^z

a [r]_C b = b [r]_C a = exp_C^[r]( exp_C^[-r](a) + exp_C^[-r](b) )

Conjecture :

a [r]_B2 b = b [r]_B2 a = exp_B2^[r]( exp_B2^[-r](a) + exp_B2^[-r](b) ) = a [r]_B1 b = b [r]_B1 a = exp_B1^[r]( exp_B1^[-r](a) + exp_B1^[-r](b) )

Or simply : a [r]_B2 b = a [r]_B1 b.

Remark : its known to be true for r a positive integer. (it fails for r = -1 though )

Unfortunately I lost some data concerning this idea.

So if you see it mentioned here before , plz let me know.

I am also intrested in other " base independance " equations.

https://sites.google.com/site/tommy1729/...e-property

regards

tommy1729